MEDIA AND MODERNITY: THE ROLE OF THE PRINTING PRESS IN THE MODERNIZATION OF WESTERN SOCIETY - Sunesti, Yuyun (Fakultas Dakwah IAIN Purwokerto, 2011)
One of the influential factors in the formation of modern society in the Westernworld and subsequently spread to over the world has been the discovery of printing presswhich can be found in the form of printing method, printing company and print media.Since it was firstly used by Gutenberg in about 15th century AD, information which waspreviously delivered through oral medium with a limited audience, then through a methodof printing can be reproduced in large quantities and can be read by more audience, acrossdistance and time. Printing method which encourages the emergence of large printingcompanies and then print media has contributed in transforming modern cultural life ofsociety.In addition, the advent of the printing industries which has transformed intotransnational corporations as well as the emergence of journals and regular newspapersalso contributes significantly in raising public spaces as a medium for discussion andcritical thinking amidst society. Ultimately, this information media transformation brings achange in the state system which is more open and leads to the emergence of ideas ofnationalism which becomes an important milestone in transforming traditional societiesinto modern societies.